2004
DOI: 10.1270/jsbbs.54.253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Controlling Cold Tolerance at the Reproductive Stage in Yunnan Landrace of Rice, Kunmingxiaobaigu

Abstract: This study focused on a Yunnan landrace of rice, Kunmingxiaobaigu, to identify quantitative trait loci (QTLs) controlling cold tolerance at the reproductive stage using DNA markers. A linkage map with 16 linkage groups covering 1,354.4 cM with a total of 122 markers was constructed based on an F 2 population consisting of 250 individuals of a cross between Kunmingxiaobaigu and a Japanese variety, Towada. Nine QTLs were detected by interval mapping in the F 2 population. The nine QTLs were distributed on chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 18 publications
3
49
0
Order By: Relevance
“…Tolerance to cold at the booting stage is one of the most genetically complex traits in rice. To date, about 40 quantitative trait loci (QTLs) located on all chromosomes have been reported in various cross combinations (Andaya and Mackill 2003, Dai et al 2004, Kuroki et al 2007, Li et al 1997, Oh et al 2004, Saito et al 1995, Suh et al 2010, Takeuchi et al 2001, Xu et al 2008. Detection of QTLs with large effects has made it possible to transfer the target QTL (or gene) into elite varieties by marker-assisted selection (MAS); however, breeding for cold tolerance has been mainly by artificial selection with conventional breeding methods because of its complex pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance to cold at the booting stage is one of the most genetically complex traits in rice. To date, about 40 quantitative trait loci (QTLs) located on all chromosomes have been reported in various cross combinations (Andaya and Mackill 2003, Dai et al 2004, Kuroki et al 2007, Li et al 1997, Oh et al 2004, Saito et al 1995, Suh et al 2010, Takeuchi et al 2001, Xu et al 2008. Detection of QTLs with large effects has made it possible to transfer the target QTL (or gene) into elite varieties by marker-assisted selection (MAS); however, breeding for cold tolerance has been mainly by artificial selection with conventional breeding methods because of its complex pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…QTL mapping studies for cold tolerance at booting stage have also been conducted on various rice populations (Andaya and Mackill 2003;Dai et al 2004;Li et al 1997Li et al , 2003Saito et al 2004Saito et al , 2001Saito et al , 1995Takeuchi et al 2001;Xu et al 2008). Saito et al (1995) mapped two QTLs for cold tolerance at the booting stage in Norin-PL8 on chromosomes 3 and 4.…”
Section: Introductionmentioning
confidence: 99%
“…Takeuchi et al (2001) identified three QTLs in a cross between two japonicas; one of the QTLs on chromosome 7 contributed 22% to the phenotypic variation. Dai et al (2004) also detected a strong QTL on chromosome 7 from a Yunnan land race. Another QTL on chromosome 4 was detected by introgressing the chromosomal fragment from the tolerant tropical japonica Silewah into the japonica variety Hokkai241.…”
Section: Low-temperature Tolerancementioning
confidence: 91%